Teachers’ Perception of ICT Use in TEFL: A Case Study in Vocational School of Surakarta - Amaliah Zahroh, Alfin; Anita Arum C.; K. Ratih; Endang F. (Samudra Publisher, 2024)
This research aims to determine the perceptions of TEFL (Teaching English as a Foreign Language) teachers in vocational schools regarding the use of Information and Communication Technology (ICT) in their classes. This study explores the potential benefits and challenges associated with ICT integration in this special educational context. The research design for this study was a mixed methods research, both qualitative and quantitative. The instruments used in this research were questionnaires and interviews. The results show that teachers generally have a positive perception of the use of ICT in their teaching process. It is hoped that by analyzing teachers' perspectives, this research aims to contribute to a deeper understanding of how ICT can be used effectively to improve EFL learning for vocational students.